The tetracycline resistome is shaped by selection for specific resistance mechanisms by each antibiotic generation - Kevin S. Blake; Yao-Peng Xue; Vincent J. Gillespie; Skye R. S. Fishbein; Niraj H. Tolia; Timothy A. Wencewicz; Gautam Dantas (Nature Communications)
Abstract The history of clinical resistance to tetracycline antibiotics is characterized by cycles whereby the deployment of a new generation of drug molecules is quickly followed by the discovery of a new mechanism of resistance. This suggests mechanism-specific selection by each tetracycline generation; however, the evolutionary dynamics of this remain unclear. Here, we evaluate 24 recombinant Escherichia coli strains expressing tetracycline resistance genes from each mechanism (efflux pumps, ribosomal protection proteins, and enzymatic inactivation) in the context of each tetracycline generation. We employ a high-throughput barcode sequencing protocol that can discriminate between strains in mixed culture and quantify their relative abundances. We find that each mechanism is preferentially selected for by specific antibiotic generations, leading to their expansion. Remarkably, the minimum inhibitory concentration associated with individual genes is secondary to resistance mechanism for inter-mechanism relative fitness, but it does explain intra-mechanism relative fitness. These patterns match the history of clinical deployment of tetracycline drugs and resistance discovery in pathogens.